THE STUDY OF METHODS OF WOOD BENDING - Pylypiv, Igor (Forestry, Forest, Paper and Woodworking Industry, 2011)
Existing methods for bending wood. The basic perspective directions of manufacturing curved details and examples of finished products. The analysis of technology, given the advantages and disadvantages of each. Using new methods of bending is one way to save wood resources.